2019
DOI: 10.2174/1566524019666190429144310
|View full text |Cite
|
Sign up to set email alerts
|

Exosome: An Emerging Source of Biomarkers for Human Diseases

Abstract: Exosomes are 30-120nm long endocytic membrane-derived vesicles, which are secreted by various types of cells and stably present in body fluids, such as plasma, urine, saliva and breast milk. Exosomes participate in intercellular communication. Recently accumulative studies have suggested that exosomes may serve as novel biomarkers for disease diagnosis and prognosis. Herein, we reviewed the biological features of exosomes, technologies for exosome isolation and identification, as well as progress in exosomal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 65 publications
0
80
0
Order By: Relevance
“…In contrast to other EVs such as apoptotic bodies, smaller exosomes (10-100 nm) are produced as intraluminal vesicles with multivesicular bodies (MVBs) and are released into the extraluminal space as a result of the fusion of MVBs with the plasma membrane [31]. Exosome secretion is a spontaneous physiological phenomenon, thought to be important for cellular integrity [32,33]. Based on their distinct content and their interactions with recipient cells, exosomes are now believed to convey 'encrypted' information [34].…”
Section: Mirs Mobility In the Tmementioning
confidence: 99%
“…In contrast to other EVs such as apoptotic bodies, smaller exosomes (10-100 nm) are produced as intraluminal vesicles with multivesicular bodies (MVBs) and are released into the extraluminal space as a result of the fusion of MVBs with the plasma membrane [31]. Exosome secretion is a spontaneous physiological phenomenon, thought to be important for cellular integrity [32,33]. Based on their distinct content and their interactions with recipient cells, exosomes are now believed to convey 'encrypted' information [34].…”
Section: Mirs Mobility In the Tmementioning
confidence: 99%
“…Exosomes are cell-derived vesicles with diameters of 30-100 nm. Studies have confirmed exosomes are present in many body fluids, including blood, urine, and saliva 4 . CircRNA have been found to be stably present in exosomes, and could serve as novel non-invasive biomarkers 5 .…”
Section: Introductionmentioning
confidence: 96%
“…Originally considered cellular waste, EXO have emerged as important ‘packets’ of molecular information, reflective of the physiologic and pathologic state of the source cell [ 120 , 121 , 122 , 123 , 124 ]. Their presence in most body fluids and content of a repertoire of proteins [ 124 , 125 , 126 , 127 ], mRNAs, and miRNAs [ 124 , 128 ] has raised excitement for potential in disease diagnostics [ 129 ]. Saliva exosomes, for example, are under intensive study for early disease biomarkers [ 130 ].…”
Section: Exosome-based Therapiesmentioning
confidence: 99%